Kegiatan Peningkatan Fungsi Fasilitas Umum melalui Revitalisasi di Area Lapangan Badminton di Lingkungan Unit Pelaksana Teknis Pengelolaan Jalan dan Jembatan Surabaya, Jalan Gayung Kebonsari No. 167, Surabaya - Novita Wulandari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Public facilities play an important role in supporting community activities, especially in sports and social interaction. However, inadequate maintenance can reduce their functionality and user comfort. This study aims to improve the function of public facilities through the revitalization of a badminton court area at the Technical Implementation Unit for Road and Bridge Management in Surabaya, making it more feasible, safe, and comfortable for use. The study employs a quantitative descriptive approach combined with Participatory Action Research (PAR), with data collected through direct observation of facility conditions before and after revitalization. The results show a significant improvement in the quality of infrastructure, both in physical condition and environmental comfort. The revitalized court supports better sports activities and increases user participation. These findings indicate that revitalization not only enhances facility quality but also promotes greater utilization, improved social interaction, and a more productive environment, demonstrating its effectiveness in optimizing public facility functions.